Berberine Alleviates Acute Lung Injury in Septic Mice by Modulating Treg/Th17 Homeostasis and Downregulating NF-κB Signaling - Chen L; Liu X; Wang X; Lu Z; Ye Y (Dove Medical Press, 2023)
Longwang Chen,1,* Xinyong Liu,2,* Xuetao Wang,3 Zhongqiu Lu,1 Yumei Ye4 1Department of Emergency, the First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, People's Republic of China; 2Department of Critical Care Medicine, Affiliated Jinhua Hospital, Zhejiang University School of Medicine, Jinhua, Zhejiang, People's Republic of China; 3Department of Intensive Care Unit, Wenzhou Longwan District First People's Hospital, Wenzhou, Zhejiang, People's Republic of China; 4Department of Ultrasound Imaging, the First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, People's Republic of China*These authors contributed equally to this workCorrespondence: Yumei Ye, Department of Ultrasound Imaging, the First Affiliated Hospital of Wenzhou Medical University, Wenzhou, 325000, People's Republic of China, Tel +860577-5557-9410, Email 314894957@qq.comPurpose: A common complication of sepsis is acute lung injury (ALI), which is associated with an acute onset, rapid disease changes, and high mortality. Regulatory T (Treg) and T helper 17 (Th17) cells comprise CD4+ T cell subsets, which strongly influence inflammation during ALI. In this study, we investigated the effect of berberine (BBR), an antioxidant, anti-inflammatory, and immunomodulatory drug, on the inflammatory response and immune state in mice with sepsis.Methods: A mouse model of cecal ligation and puncture (CLP) was established. The mice were intragastrically administered 50 mg/kg BBR. We used histological techniques to evaluate inflammatory tissue injury and flow cytometry for analyzing Treg/Th17 levels. We also assessed NF-κB signaling pathways by Western blotting assays and immunofluorescence staining. Enzyme-linked immunosorbent assay (ELISA) was performed to measure the content of cytokines.Results: Treatment with BBR considerably mitigated lung injury while improving survival, post-cecal ligation, and puncture (CLP). Treatment with BBR ameliorated pulmonary edema and hypoxemia in septic mice and inhibited the NF-κB signaling pathway. BBR also increased Treg cells and decreased Th17 proportions in the spleen and lung tissue of CLP-treated mice. Blocking Treg cells weakened the protective effect of BBR on sepsis-associated lung injury.Conclusion: Overall, these results suggested that BBR is a potential therapeutic agent for sepsis.Graphical Abstract: Keywords: berberine, sepsis, inflammation, cell differentiation, immunodeficiency, T lymphocyte